The marketing mix equilibrium in the development and control management structure - Stetsenko, Victoria (My University, 2013)
Derived indicator for the marketing mix equilibrium has been presented in the article along with improved classification of varieties of marketing control by means of equilibrium control. У статті розроблено показник збалансованості маркетингового комплексу, удосконалено класифікацію видів маркетингового контролю шляхом введення контролю збалансованості.
Keywords: balance of marketing mix; business development; marketing control; збалансованість маркетингового комплексу; розвиток підприємства; маркетинговий контроль; сбалансированность маркетингового комплекса; развитие предприятия; маркетинговый контроль; кафедра маркетингу